2015
DOI: 10.26493/1855-3974.502.566
|View full text |Cite
|
Sign up to set email alerts
|

Quartic integral Cayley graphs

Abstract: We give exhaustive lists of connected 4-regular integral Cayley graphs and connected 4-regular integral arc-transitive graphs. An integral graph is a graph for which all eigenvalues are integers. A Cayley graph Cay(Γ, S) for a given group Γ and connection set S ⊂ Γ is the graph with vertex set Γ and with a connected to b if and only if ba −1 ∈ S. Up to isomorphism, we find that there are 32 connected quartic integral Cayley graphs, 17 of which are bipartite. Many of these can be realized in a number of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In 2015, Minchenko and Wanless [243] proved that up to isomorphism there are precisely 32 connected 4-regular integral Cayley graphs, 17 of which are bipartite. They also proved that there are exactly 27 arc-transitive 4-regular integral graphs of degree 4, 16 of which are bipartite.…”
Section: Integral Cayley Graphs Of Small Degreesmentioning
confidence: 99%
“…In 2015, Minchenko and Wanless [243] proved that up to isomorphism there are precisely 32 connected 4-regular integral Cayley graphs, 17 of which are bipartite. They also proved that there are exactly 27 arc-transitive 4-regular integral graphs of degree 4, 16 of which are bipartite.…”
Section: Integral Cayley Graphs Of Small Degreesmentioning
confidence: 99%
“…Since G ∈ G 4 , Cay( a, b , {a, a −1 , b, b −1 }) is a quartic connected integral graph. Note that all quartic connected Cayley integral graphs were obtained in [19]. Observe that a b = a −1 .…”
Section: Classes a 3 And Gmentioning
confidence: 99%
“…In 2015, M. Minchenko and I. M. Wanless [12] investigated 4-regular integral Cayley graphs. It was shown that up to isomorphism, there are 32 connected 4-regular integral Cayley graphs (17 of them are bipartite) and 27 connected 4-regular integral arc-transitive graphs (16 of them are bipartite, and 16 of them are Cayley graphs).…”
Section: Introductionmentioning
confidence: 99%